Public Pedagogy and the Archive: Information, Interruption, and Public Things amidst Canadian Housing Activism - Martin, Timothy (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2025)
The Toronto Disaster Relief Committee (TDRC) was a coalition of housing activists active in the years between 1998 and 2012 (Monsebraaten, 2012; Toronto Disaster Relief Committee, 1998, 2012). Their efforts bore witness to the rise of dehousing (Hulchanski, 2000, 2010), and the associated trauma and deaths of those forced to live without housing. Upon their closure, they donated their collective files to the City of Toronto Archives. This paper articulates how the curation and public provision of their collected material operates as a significant form of public pedagogy. First, the TDRC files are what I term a “counter-archive within.” That is, nested within a conventional archive, often figured as a repository for colonial common sense, motivated by the preservation of state power (Stoler, 2002), lies a counternarrative that challenges the epistemic authority of neoliberal logic. Secondly, in tandem with monthly public events, such an archive resists the “re-scripting” (Edkins, 2003, p. xv) of trauma in commemorative practice; activists as archivists unveil the faults in state-managed temporal arrangements. And finally, the storing of such material in a public institution like the Toronto Archives ultimately foregrounds the archive as a public thing (Honig, 2017) that requires our contestation, care, and attention.